2007
DOI: 10.1021/om700857j
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Properties of N-Heterocyclic Carbene (NHC) Ligands:  Synthetic, Structural, and Spectroscopic Studies of (NHC)Platinum(II) Complexes

Abstract: N-Heterocyclic carbene complexes of platinum (II) have been synthesized, notably monocarbene complexes cis-[(IPr)Pt(dmso)(Cl) 2 ], 6, cis-[(IMes)Pt(dmso)(Cl) 2 ], 7, cis-[(SIPr)Pt(dmso)(Cl) 2 ], 8, cis-[(SIMes)Pt(dmso)(Cl) 2 ], 9, and cis-[(TTP)Pt(dmso)(Cl) 2 ], 10. All complexes have been fully characterized by multinuclear NMR spectroscopy. Complex 7, 9, and 10 have been characterized by X-ray crystallography. The data obtained have allowed for the differentiation between electronic contributions (σ and π) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
162
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(179 citation statements)
references
References 67 publications
13
162
0
2
Order By: Relevance
“…These observations are consistent with previous experimental and computational work on some Pt II complexes, for which NMR spectroscopy and an energy decomposition analysis (EDA) have suggested a large backbonding contribution. [88] Finally, the computed values in the square-planar PdI 2 (PH 3 )(NHC) complex and model Grubbs metathesis precatalyst are also much larger than zero, but more modest than for the Pd 0 and Pt 0 cases, as expected from the structural analysis. Attempts to calculate the backbonding contributions in Ir(CH 2 )Cp(NHC) were thwarted by the fact that it was not possible to select an appropriate Lewis reference structure to describe the metal-Cp bonding.…”
Section: Nbo Analysismentioning
confidence: 62%
“…These observations are consistent with previous experimental and computational work on some Pt II complexes, for which NMR spectroscopy and an energy decomposition analysis (EDA) have suggested a large backbonding contribution. [88] Finally, the computed values in the square-planar PdI 2 (PH 3 )(NHC) complex and model Grubbs metathesis precatalyst are also much larger than zero, but more modest than for the Pd 0 and Pt 0 cases, as expected from the structural analysis. Attempts to calculate the backbonding contributions in Ir(CH 2 )Cp(NHC) were thwarted by the fact that it was not possible to select an appropriate Lewis reference structure to describe the metal-Cp bonding.…”
Section: Nbo Analysismentioning
confidence: 62%
“…For comparison, in Figure 4, formed from the reaction between the free imidazolin-2-ylidines and methanol, [10] the 1 H and 13 C NMR chemical shifts of the NC(H)N fragment are d = 5.48 ppm and 104 ppm respectively. In the zwitterionic unsaturated analogue OCMe 2 CH 2 {1-CHNCHCHNiPr} reported by us, [24] the 1 H and 13 C NMR chemical shifts of the NC(H)N fragment are d = 7.77 ppm and 199 ppm, respectively, suggesting that adducts 2 R do not exist as zwitterionic imidazolinium alkoxides.…”
Section: Thementioning
confidence: 86%
“…[12] Another study showed that the saturated NHCs are better acceptors of p-back-donation than the unsaturated analogues in Pt II complexes, which contain a bonding contribution of about 10 % from back-bonding. [13] Most recently, studies on an iridium system that allows for a direct comparison of a wide range of monodentate carbenes, [IrA C H T U N G T R E N N U N G (NHC)(CO) 2 Cl], have again concluded that the differences between the two types of NHC are very small, and the sterics of the ligands probably provide the greatest contribution to differences in the complexes formed. [14] A number of synthetic routes to substituted imidazolinium proligands have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Veränderungen der Elemente,die sich in Nachbarschaft zum Carben-C-Atom befinden, ebenso wie die Grçße und Sätti-gung des Ringes oder das Substitutionsmuster des Rückgrats bewirken signifikante elektronische Unterschiede in der sDonorstärke des freien Elektronenpaars und der p-Akzeptorfähigkeit des formal leeren p-Orbitals des Carben-CAtoms.Zusätzlich zu den zahlreichen theoretischen Studien, welche die elektronischen Eigenschaften von stabilen Carbenen miteinander vergleichen, [3] wurden auch vielfältige experimentelle Methoden entwickelt, um die entsprechenden Donor/Akzeptor-Eigenschaften zu quantifizieren. [4] NMRspektroskopische Experimente,i nd enen die 31 P-, 77 Se-oder 13 C-NMR-Signale von Carben-Phosphinidin-, [5] Carben-Selenid- [6] oder Carben-Platin-Komplexen [7] verglichen wurden, sind ein nützliches Hilfsmittel zur Einstufung des Carbencharakters.E benso konnte durch rçntgenstrukturelle, schwingungsspektroskopische und elektrochemische Messungen von Organometallkomplexen verschiedener Carbene eine Fülle an Informationen erhalten werden. [4,8] In den vergangenen Jahren berichteten wir über die Synthesen von zwei ähnlichen Verbindungen, die durch Carbene mit unterschiedlichen elektronischen Eigenschaften stabilisiert wurden.…”
unclassified
“…Die bereits erwähnten Vergleichsstudien von Carbenen zeigten, dass SIDip,d as sich von IDip durch ein gesättigtes Rückgrat unterscheidet, eine hçhere p-Acidität als jenes,j edoch eine wesentlich geringere als CAAC aufweist (Schema 1). [5][6][7] Die Reduktion von 1,2-(SIDip) 2 -B 2 Br 4 )d urch Natriumnaphthalid ergab 3 in moderater Ausbeute.I nÜ bereinstimmung mit vorangegangenen NMR-Studien zeigte das 11 B-NMR-Spektrum ein Signal für 3 bei d = 58 ppm, das zwischen dem von 1 (d = 39 ppm) und dem von 2 (d = 80 ppm) liegt. [5][6][7] Geeignete Einkristalle für die Rçntgenstrukturanalyse konnten durch langsames Abdampfen einer Benzollçsung erhalten werden (Abbildung 1a).…”
unclassified